Descope of the ALIA mission. (April 2015) - Gong, Xuefei; Lau, Yun-Kau; Xu, Shengnian; Amaro-Seoane, Pau; Bai, Shan; Bian, Xing; Cao, Zhoujian; Chen, Gerui; Chen, Xian; Ding, Yanwei; Dong, Peng; Gao, Wei; et al.
Abstract: The present work reports on a feasibility study commissioned by the Chinese Academy of Sciences of China to explore various possible mission options to detect gravitational waves in space alternative to that of the eLISA/LISA mission concept. Based on the relative merits assigned to science and technological viability, a few representative mission options descoped from the ALIA mission are considered. A semi-analytic Monte Carlo simulation is carried out to understand the cosmic black hole merger histories and the possible scientific merits of the mission options in probing the light seed black holes and their coevolution with galaxies in early Universe. The study indicates that, by choosing the armlength of the interferometer to be three million kilometers and shifting the sensitivity floor to around one-hundredth Hz, together with a very moderate improvement on the position noise budget, there are certain mission options capable of exploring light seed, intermediate mass black hole binaries at high redshift that are not readily accessible to eLISA/LISA, and yet the technological requirements seem to within reach in the next few decades for China.